Treatment of time‐dependent effects in molecular junctions. Issue 11 (7th August 2013) - Popescu, Bogdan; Kleinekathöfer, Ulrich; Frauenheim, Thomas; Niehaus, Thomas; Repp, Jascha; Richter, Klaus; Weber, Heiko
<x xml:space="preserve">Abstract</x> The current through molecular junctions can be influenced by various time‐dependent perturbations. Among these are external (laser) fields and fluctuating environments. Both types of external perturbations can lead to large and fast fluctuations of the site energies and electronic couplings involved in the charge transfer. In these cases, theoretical approaches have to be utilized which can accurately and efficiently determine the resulting strongly time‐dependent charge current. To this end we review different formalisms based on the decomposition of the spectral density and the Fermi function, i.e., a standard perturbative approach to second and fourth‐order, a hierarchical theory as well as a nonequilibrium Green's function formalism. The accuracy of the different approaches for the single resonant level model is numerically studied. In an additional test, the electronic level is driven in order to analyze the accuracy for time‐dependent scenarios. Moreover, the results for a multi‐site setup with strongly fluctuating levels are analyzed and compared to a snapshot‐averaged Landauer approach.